2022
DOI: 10.1111/jog.15527
|View full text |Cite
|
Sign up to set email alerts
|

Clinical feasibility of absorbable gelatin film adhesion barrier (GM142TENALEAF®”) in gynecological laparoscopic surgery: Safety assessment for first‐in‐human use and surgical video

Abstract: Aim To evaluate the safety and operability of the GM142 (TENALEAF®, Medical Division, Gunze Limited, Tokyo, Japan) adhesion barrier applied in patients undergoing surgery for benign gynecologic disease. Methods This multicenter open study enrolled 34 patients from November 2018 to October 2019. Results The primary outcome was the incidence of adverse events (AE) within 12 weeks postoperatively. None of the 30 patients completing the study experienced a life‐threatening AE. Thirteen patients (43.3%) suffered 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, this difference did not show superiority [67]. A clinical feasibility trial in gynecological laparoscopic surgery patients demonstrated safety [68].…”
Section: Tenaleaf Bioabsorbable Thermally Cross-linked Gelatin Filmmentioning
confidence: 90%
“…However, this difference did not show superiority [67]. A clinical feasibility trial in gynecological laparoscopic surgery patients demonstrated safety [68].…”
Section: Tenaleaf Bioabsorbable Thermally Cross-linked Gelatin Filmmentioning
confidence: 90%